Reward-punishment sensitivity bias predicts narcissism subtypes: Implications for the etiology of narcissistic personalities. (15th April 2019) - Miles, Gabrielle J.; Smyrnios, Kosmas X.; Jackson, Mervyn; Francis, Andrew J.P.
Abstract: Etiology for narcissism is undetermined, although associations have been reported between subtypes of narcissism and Gray's (1970, revised 2000) biologically based behavioral approach (BAS) and behavioral avoidance (BIS) systems of personality. Two studies (N = 199, N = 151) investigated Australian community families for associations between grandiose narcissism, vulnerable narcissism, BAS, BIS, and motivational bias indexed by z -transformed BAS less z -transformed BIS (zBLB). Grandiose, but not vulnerable, narcissism was substantially and significantly associated with approach motivational bias, while the vulnerable subtype was associated relatively more strongly with BIS than BAS. These results suggest that: (1) approach motivational bias may be critical to grandiose, but not vulnerable narcissism development, and (2) vulnerable narcissism development may be influenced by other (yet to be determined) factors in addition to possible influences of BIS and BAS. Furthermore, since asymmetrical brain EEG activity as well as asymmetrical dopamine D2 receptor binding have recently been associated with approach-avoidance motivational bias (zBLB) 1 rather than absolute BAS or BIS values, we theorize an alternate etiology for narcissism: that the biology underpinning BAS and BIS may also influence development of approach and avoidance orientation aspects of narcissism, and may precede narcissism development, particularly the grandiose form. Highlights: Approach-avoidance motivation bias significantly predicted grandiose narcissism. Approach-avoidance motivation bias was not associated with vulnerable narcissism. Absolute levels of BAS and BIS differentially predicted narcissism subtypes. High BAS and low BIS predicted grandiose narcissism. Moderate BAS and high BIS predicted vulnerable narcissism.